1984
DOI: 10.1302/0301-620x.66b4.6746698
|View full text |Cite
|
Sign up to set email alerts
|

Experimental epiphysial distraction producing and correcting angular deformities

Abstract: Angular deformities of the distal radius of 15 sheep were induced by asymmetrical epiphysial distraction. Eleven sheep were between 10 and 20 weeks old; four were older than 24 weeks. Gradual distraction on the medial side of the limb caused partial separation of the epiphysis from the metaphysis, resulting in a valgus deformity. The distraction device was removed three to six weeks after insertion. Spontaneous correction of angulation with growth occurred in the younger sheep; but when the induced valgus angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Unfortunately, equivocal results have been reported in the numerous animal (3,5,7,9,10, 14,15,17,20) and clinical studies (4,6,11) using transphyseal tension to correct acquired deformity.…”
mentioning
confidence: 99%
“…Unfortunately, equivocal results have been reported in the numerous animal (3,5,7,9,10, 14,15,17,20) and clinical studies (4,6,11) using transphyseal tension to correct acquired deformity.…”
mentioning
confidence: 99%
“…It has also been suggested that the harmful effects.of the distraction are dependent on the rate of distraction and the force used to cause the physeal separation (De Bastiani et al 1986, de Pablos et al 1986). Peltonen et al (1984b) observed that separation of the physis occurred more easily in younger animals and that the healing was also rapid. Complications were also more common in animals closer to skeletal maturity.…”
Section: Discussionmentioning
confidence: 92%
“…4,5,13,15 The goal of the present work is to offer a review of the clinical experience with physeal distraction for the treatment of angular deformities of the long bones during the period from 1982 to 1989 and to offer what is believed to be some useful conclusions for future application.…”
Section: Introductionmentioning
confidence: 99%